The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/ijcma-03-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relationality toward congruence: a symbiotic solution to cross-cultural negotiations

Abstract: Purpose This paper aims to advance an integrative perspective of dynamic relationality in negotiation research by providing a symbiotic solution to modeling the cultural adaptation process in intercultural negotiations. Design/methodology/approach Based on a solution-oriented symbiotic approach, the authors analyze negotiators’ combination strategy to propose the dynamic convergence of dyadic relational negotiation behavior (RNB) both as a descriptive framework and a prescriptive solution to behavioral congr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Previous research studies on conflict management usually study the conflict in international affairs and negotiations (Cheng, 2019) or stakeholder conflicts (Irfan et al, 2019). Literature regarding the business and government conflicts lacks an evolutionary and dynamic perspective toward the interactions between them.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research studies on conflict management usually study the conflict in international affairs and negotiations (Cheng, 2019) or stakeholder conflicts (Irfan et al, 2019). Literature regarding the business and government conflicts lacks an evolutionary and dynamic perspective toward the interactions between them.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the adaptation of a country's culture, the traditional dress adaptation is much simpler and is widely observed. In a recent study, Cheng (2019) concluded that the consumers' explorative behaviour in food and fashion is significantly influenced by CA. In her study, she stretches this point by illustrating how a Chinese restaurant offers a different range of halal food to attract Muslim consumers.…”
Section: Cultural Adaptationmentioning
confidence: 99%